ISTIKHDĀM TIKNULUJIYYĀ AL MA’LŪMĀT WA AL ITTISHĀLĀT FÎ TA’LLUM AL LUGHAH AL ‘ARABIYYAH FÎ AL JĀMI’AH AL ISLĀMIYYAH - Rosyadi, Faiq Ilham (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2020)
This research is useful to discuss the use of information and communication technology in Arabic learning in Islamic University by using the literature study method with a qualitative descriptive approach. Data sources in this research are research literature and theory books. This study aims to obtain written information related to the use of information and communication technology as a media for Arabic learning in Islamic University. In addition to answering questions about the media that can be used in Arabic learning as an effort by Islamic Universities to make Arabic easy to understand, to know, to practice and like students in their learning. The researcher concludes that with advances in information and communication technology, Arabic lecturers must be able to develop effective Arabic learning models in an Islamic university, and use appropriate methods to realize learning objectives and use media that are compatible with learning methods that are accordance with information and communication technology advancement. information. The development of technology and communication provide great potential to change the way students learn and obtain information. Various learning media that can be used for effective Arabic learning are computer, internet, television, and Arabic e-learning. Keywords: Information and Communication Technology, Media, Learning, Arabic.